2019
DOI: 10.1021/acsmacrolett.9b00015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Stress Relaxation and Moderate Temperature of Malleability Enabled by the Synergy of Disulfide Metathesis and Carboxylate Transesterification in Epoxy Vitrimers

Abstract: Vitrimers make up a class of polymeric materials combining the advantages of thermosets and thermoplastics, because they can be reprocessed while being at the same time permanently cross-linked. However, a long heating duration or an elevated temperature is necessary for most vitrimers to relax the stress from deformation and exhibit malleability. Herein, a disulfide-containing carboxylic acid is applied as a curing agent to synthesize epoxy vitrimers with simultaneous disulfide metathesis and carboxylate tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
247
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(258 citation statements)
references
References 42 publications
10
247
1
Order By: Relevance
“…5a). 49 Also, Dichtel and co-workers observed that applying the disulde exchange in polyhydroxyurethane networks resulted in more rapid reprocessing of PHU networks, i.e. within 30 min at about 150 C (Fig.…”
Section: Vitrimer Hybrids: Combination Of Dynamic Bond Exchanges and mentioning
confidence: 93%
“…5a). 49 Also, Dichtel and co-workers observed that applying the disulde exchange in polyhydroxyurethane networks resulted in more rapid reprocessing of PHU networks, i.e. within 30 min at about 150 C (Fig.…”
Section: Vitrimer Hybrids: Combination Of Dynamic Bond Exchanges and mentioning
confidence: 93%
“…By using a disulfide‐containing carboxylic acid as a crosslinker in epoxy vitrimers, simultaneous disulfide metathesis and carboxylate transesterification were enabled. Among other desirable outcomes, full recovery of mechanical strength for at least four cycles at 100 °C in 1 h was achieved 69. Aside from synergistic approaches, the relevant literature continually relays examples of new chemistries, or new variations of old chemistries.…”
Section: Stimuli Responsiveness Of Cansmentioning
confidence: 99%
“…Other studies explored the properties of vitrimer composites and the addition of nondynamic cross-links to the network. 14,28,29,30,31,32,33,34,35 These research efforts established that modifying vitrimer chemistry provides a pathway for tuning mechanical properties, 36,37,38 stress relaxation, 39,40,41,42 shape memory, 43,44,45 and the ability to self-heal and adhere to other materials. 21,46 Due to this versatility, vitrimers are now being tested for a variety of high-end applications.…”
mentioning
confidence: 99%